Leveraging the learning focal point algorithm for emotional intelligence - Mansour, Salah Eddine; Sakhi, Abdelhak; Kzaz, Larbi; Sekkaki, Abderrahim (Institute of Advanced Engineering and Science, 2024)
One of the secrets of the success of the education process is taking into account the learner’s feelings. That is, the teacher must be characterized by high emotional intelligence (EI) to understand the student’s feelings in order to facilitate the indoctrination process for him. Within the framework of the project to create a robot teacher, we had to add this feature because of its importance. In this article, we create a computer application that classifies students' emotions based on deep learning and learning focal point (LFP) algorithm by analyzing facial expressions. That is, the robot will be able to know whether the student is happy, excited, or sad in order to deal with him appropriately.